2020
DOI: 10.1002/jor.24941
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity is associated with the glenohumeral synovitis in patients with a rotator cuff tear

Abstract: Synovitis of the glenohumeral joint (GHJ) and subacromial space (SAS) is one of the most common findings during arthroscopic rotator cuff repair (RCR). The purpose of this study is to determine clinical factors associated with the degree of synovitis in patients with a rotator cuff tear and whether macroscopic synovitis affects early clinical outcomes following arthroscopic RCR. Arthroscopic videos of 230 patients treated with arthroscopic RCR were randomly reviewed by two experienced shoulder surgeons. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Furthermore, our results showed that PSV in the AHCA correlated with synovitis in the SAS, which is a novel finding. Several previous studies evaluated synovitis in the GHJ and SAS separately [ 3 , 20 ] and showed that the effect on pain and function differed according to the degree of synovitis in these two sites. Therefore, it would be clinically relevant to evaluate and analyze GHJ and SAS synovitis severity separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results showed that PSV in the AHCA correlated with synovitis in the SAS, which is a novel finding. Several previous studies evaluated synovitis in the GHJ and SAS separately [ 3 , 20 ] and showed that the effect on pain and function differed according to the degree of synovitis in these two sites. Therefore, it would be clinically relevant to evaluate and analyze GHJ and SAS synovitis severity separately.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most common pathologies encountered during arthroscopic surgery in patients with RCTs is synovitis of the glenohumeral joint (GHJ) and subacromial space (SAS). In recent years, intraoperative grading systems for synovitis haves been established [ 1 , 2 ], and synovitis grade has been shown to have clinical relevance in contributing to pain and dysfunction in patients with RCTs [ 3 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lateral portion of the glenohumeral joint capsule receives its blood supply from the AHCA [ 11 ], and increased blood flow velocity in the AHCA has been reported to reflect synovitis in this area [ 7 ]. Recent studies have indicated that severe synovitis in the glenohumeral joint may be involved in the pathogenesis of pain [ 12 , 13 ]. Thus, our finding that blood flow velocity, which may reflect synovitis, was increased during the severe night pain phase in the patient after ARCR coincides with a recent study on RCT patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified subacromial and glenohumeral synovitis as being a source of pain in rotator cuff disease. 1 , 3 , 12 , 16 , 20 Moreover, glenohumeral synovitis would be associated with early postoperative shoulder stiffness after ARCR. 29 Management of synovitis in the shoulder joint is one of the most important factors in the treatment of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathology of shoulder pain is still controversial, several studies have reported subacromial and glenohumeral synovitis as being a source of pain in rotator cuff disease. 1 , 3 , 12 , 16 , 20 Being female, age less than 50 years old, workers' compensation, diabetes, patients with partial tears, preoperative pain, and adhesive capsulitis have been reported as predictive factors for shoulder stiffness after ARCR. 13 , 14 , 25 , 30 Glenohumeral synovitis would be associated with early postoperative shoulder stiffness after ARCR.…”
mentioning
confidence: 99%